Evaluation of the use of antibiotics in a health area. (European Journal of Health Research, 2020)
The use of antibiotics is one of the main tools for the therapeutic management of most infections of bacterial origin. It is excessive and unnecessary use can cause damage to both public and individual health. The work that we present part of the research carried out in a health area with a population of about 84 thousand inhabitants. The main objective was to analyze the use of antibiotic drugs in our health area, global consumption and the consumption according to the type of antibiotic. Secondary objective was to compare the results obtained with the results reflected at the national level. Data were obtained through an electronic medical prescription billing software and the dose per inhabitant per day (DHD) measurement variable was used. The results showed that in our health area a lower use of antibiotics is observed in comparison with the data available nationwide, average consumption of antibiotics in Spain in the outpatient setting in 2017 was 16.13 DHD versus 15.22 DHD in our area